Elimination of cracks in Al–Zn–Mg–Cu alloy by addition of TiO2 in selective laser melting - Biao Huang; Hongqun Tang; Jun Cao; Jincheng Huang; Fei Peng; Xu Zheng; Kezhun He; Qizhong Zhao (Journal of Materials Research and Technology, 2024)
7050 aluminium alloy is widely used in aerospace industry due to its excellent mechanical properties. 7050 aluminium alloy belongs to Al–Zn–Mg–Cu alloy. Due to the formation of cracks in selective laser melting (SLM) forming of Al–Zn–Mg–Cu alloys, 7050 aluminium alloy is difficult to be applied to forming and manufacturing in this technological field. In order to solve this critical problem, in this paper, titanium dioxide (TiO2) powder was mixed with 7050 aluminium alloy using ball milling method to achieve the effect of eliminating cracks. The cracks in the specimens completely disappeared when the TiO2 additions were 1.5 wt% and 2 wt%. With the addition of TiO2, the grains gradually changed from coarse columnar crystals to fine equiaxed crystals. Combined with the temperature field simulation, the grain refinement and crack elimination mechanism of TiO2 in SLM forming were analysed. The grain refinement is attributed to the formation of Al3Ti. The crack elimination was attributed to the reduction of the intergranular solid-liquid channel length. The maximum values of tensile strength and elongation of 7050 aluminium alloy formed by SLM are achieved at 2 wt% of TiO2. The values are 389 MPa and 8.8 %. The better mechanical properties were attributed to the synergistic effect of crack elimination, Hall-Petch, and Orowan strengthening. This study provides experimental guidance for the preparation of crack-free 7050 aluminium alloy.